BENEFITS OF AUDIT QUALITY: EVIDENCE FROM INDONESIA - Jumaiyah, Jumaiyah (Fakultas Ekonomi Universitas Kadiri, 2024)
The audit opinion and the financial statement presentation are inextricably linked; the auditor cannot be blind to the facts surrounding the organization. As a result, the factors influencing the audit quality of manufacturing enterprises in the consumer product industry sector are experimentally examined in this study. This study covers the Indonesian Stock Exchange (IDX) from 2018 to 2021. The study's independent variables include audit committees, tenure audits, rotational audits, cost audits, and auditor gender. The research samples consist of all manufacturing companies in the consumer goods industry sector that have registered on the IDX up to 60 times. In this study, the sample technique employed was purposeful sampling. The IDX lists four research periods and 32 manufacturing businesses in the Goods Industry Sector, for a total of 128 samples. According to the findings, shareholders must also give corporate managers permission to charge reasonable audit fees. This audit fee may be one of the reasons why shareholders would want high-quality audits from auditors.